Bentuk dan Perkembangan Tindak Pidana Narkotika di Masa Pandemi Covid-19: Studi Kasus Putusan Pengadilan - Muhammad Djaelani Prasetya; Iustika Puspa Sari; Syahril Said; Andi Akbar (SIGn Jurnal Hukum, 2022)
This study aims to examine and analyze the juridical and victimological correlations to the forms and developments of narcotics crime based on several Decisions of the District Court of Makassar during the Covid-19 pandemic. This study uses normative legal research with a statute approach and a case approach. The collected legal material is analyzed using qualitative analysis techniques to describe the problem and answer study purposes. The results show juridical and victimological correlations: Law No. 8 of 1981, Law No. 35 of 2009, and Rehabilitation. The forms and developments of narcotics crime during the Covid-19 pandemic can be identified based on the application of investigator testimony, victims of abusers, rehabilitation, participation, criminal disparity, special minimum punishment, undercover buying, and the best interest principle for children. Therefore, it is recommended that all law enforcement agencies not abuse their authority in implementing the juridical and victimological correlations. In this case, eradicating narcotics crimes in Indonesia can be more effective in the future.